The Development of the Functional Literacy Experience Scale based upon Ecological Theory (FLESBUET) and Validity-Reliability Study - DOĞAN, MİDRABİ CİHANGİR (EDAM, 2014)
This study aims to perform a validity-reliability test by developing the Functional Literacy Experience Scale based upon Ecological Theory (FLESBUET) for primary education students. The study group includes 209 fifth grade students at Sabri Taskin Primary School in the Kartal District of Istanbul, Turkey during the 2010-2011 academic year. Structure validity of scale is examined with exploratory factor analysis and first factor is named as school, second factor as family and third factor as environment in accordance with Ecological Theory. Cronbach's alpha internal consistency coefficient, item total and residual item correlation in relation to scale are figured out. Then, significance of difference between top 27% and bottom 27% group item average and relation between item discrimination and two practices have been examined. Total Cronbach alpha value of this scale accounts for .86 and total item value is between .26-.56. t-test results are of no significance, with the difference between the top 27% and the bottom 27% of the group's item average being significant, correlation value between two practices is high and there is a significant relation at .001 level as a result. All these results put forth that Functional Literacy Experience Scale based upon Ecological Theory (FLESBUET) is valid and reliable scale for education sector.
Keywords: Ecological Theory; Functional Literacy; Literacy; Reliability; Validity